2023
DOI: 10.1002/1873-3468.14731
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a Lactobacillus helveticus chlorogenic acid esterase and the dynamics of its insertion domain provide insights into substrate binding

Kellie K. Omori,
Charles T. Drucker,
Tracie L. S. Okumura
et al.

Abstract: Chlorogenic acid esterases (ChlEs) are a useful class of enzymes that hydrolyze chlorogenic acid (CGA) into caffeic and quinic acids. ChlEs can break down CGA in foods to improve their sensory properties and release caffeic acid in the digestive system to improve the absorption of bioactive compounds. This work presents the structure, molecular dynamics, and biochemical characterization of a ChlE from Lactobacillus helveticus (Lh). Molecular dynamics simulations suggest that substrate access to the active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…An interesting finding was that quinic acid was detected in all FMPs, whereas it was not detected in fresh and control samples. A study showed that chlorogenic acid esterase in Lactobacillus helveticus had the ability to split chlorogenic acid into caffeic acid and quinic acid (Omori et al, 2023). Subsequent reduction or oxidation reactions metabolized quinic acid into shikimic acid and 3,4,5-trihydroxycyclohexane-1-carboxylic acid, or protocatechuic acid and catechol (Markkinen et al, 2022).…”
Section: Taste Compoundsmentioning
confidence: 99%
“…An interesting finding was that quinic acid was detected in all FMPs, whereas it was not detected in fresh and control samples. A study showed that chlorogenic acid esterase in Lactobacillus helveticus had the ability to split chlorogenic acid into caffeic acid and quinic acid (Omori et al, 2023). Subsequent reduction or oxidation reactions metabolized quinic acid into shikimic acid and 3,4,5-trihydroxycyclohexane-1-carboxylic acid, or protocatechuic acid and catechol (Markkinen et al, 2022).…”
Section: Taste Compoundsmentioning
confidence: 99%